Perioperative Considerations for ASD Device Closure in the First Trimester: A Case of Secundum ASD with Bidirectional Shunt - Nugroho, Yusuf Agung; Isngadi; Ruddi Hartono (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Atrial septal defect (ASD) closure during pregnancy is a complex procedure requiring careful consideration of maternal and fetal risks. This case report highlights the perioperative management of a secundum ASD with a bidirectional shunt in a patient during her first trimester. Case presentation: A 31-year-old woman, G3P2A0, presented at approximately 10-11 weeks gestation with a recently diagnosed large secundum ASD and pulmonary hypertension. She was on Sildenafil and Bisoprolol. Due to the potential risks associated with an unrepaired ASD during pregnancy, the decision was made to proceed with percutaneous ASD closure. General anesthesia was administered with meticulous hemodynamic monitoring. The procedure was successful, and the patient recovered without complications. Conclusion: ASD closure during the first trimester can be safely performed with careful planning and execution. Multidisciplinary collaboration and vigilant monitoring are crucial for optimal maternal and fetal outcomes.